2011
DOI: 10.1002/cncr.27396
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of MYC, BCL2, and BCL6 rearrangements in patients with diffuse large B‐cell lymphoma treated with cyclophosphamide, doxorubicin, vincristine, and prednisone plus rituximab

Abstract: BACKGROUND: Diffuse large B-cell lymphomas (DLBCLs) are a biologically heterogeneous group in which various gene alterations have been reported. The aim of this study was to investigate the frequency and prognostic impact of BCL2, BCL6, and MYC rearrangements in cyclophosphamide, doxorubicin, vincristine, and prednisone plus rituximab (R-CHOP)-treated DLBCL cases. METHODS: Tissue microarrays were constructed from 239 cases of DLBCL, and the expressions of CD10, BCL6, MUM1/IRF4, and BCL2 were evaluated by immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
108
1
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(128 citation statements)
references
References 40 publications
13
108
1
6
Order By: Relevance
“…However, several more recent studies within which R-CHOP-treated patients were analyzed revealed that the cell of origin, i.e. GCB or non-GCB phenotype, had no prognostic impact and no difference in OS was observed [32][33][34]. Discrepancies between studies may be explained by the addition of rituximab to chemotherapy, which may modify the prognostic impact of BCL-2 or BCL-6 protein expressions [33,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…However, several more recent studies within which R-CHOP-treated patients were analyzed revealed that the cell of origin, i.e. GCB or non-GCB phenotype, had no prognostic impact and no difference in OS was observed [32][33][34]. Discrepancies between studies may be explained by the addition of rituximab to chemotherapy, which may modify the prognostic impact of BCL-2 or BCL-6 protein expressions [33,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, there were 14 genetic double-hit and triple-hit cases out of 39 MYC rearranged diffuse large B-cell lymphomas (36%), which is within the range of published series. [14][15][16]20 BCL6/MYC genetic double-hit cases were not associated with any specific clinicopathological parameters or outcome and were not considered further.…”
Section: Fluorescence In Situ Hybridizationmentioning
confidence: 99%
“…17 More recently, the prognostic significance of MYC translocations has been challenged by the recognition of so-called phenotypic double-hit diffuse large B-cell lymphoma. 14,[18][19][20][21] To date, no study has been sufficiently statistically powered to resolve the current debatable issues regarding MYC aberrations in diffuse large B-cell lymphoma and the significance of genetic MYC single-hits vs double-hits in the context of phenotypic double-hits. The goal of this study was to address the above issues in a large number of patients with de novo diffuse large B-cell lymphoma, who were treated with R-CHOP, and stratified according to cell of origin.…”
mentioning
confidence: 99%
“…UHOD Number: 2 Volume: 23 Year: 2013 pact of some of these prognostic factors 7,[16][17][18][19] , while prognostic value of some (i.e. GC, non-GC phenotype) remains controversial.…”
mentioning
confidence: 99%
“…7,15 Double-hit and triple-hit lymphomas have had a poor response to R-CHOP therapy. 18 Some markers such as beclin-1 were shown to be the predictors of favorable clinical outcome in patients treated with R-CHOP. 20 Fascin was shown to be a poor prognostic factor in certain epithelial tumors due to its role cell adhesion, cell motility and invasiveness.…”
mentioning
confidence: 99%